High temperature cyclic oxidation of Ti-Al based intermetallic in static laboratory air - Amrin, Astuty; Hamzah, Esah; Mohd. Badri, Nurfashahidayu; Hamzah, Hafida (2007)
The objective of this study is to investigate the oxidation behavior of binary ?-TiAl based intermetallic; with composition (at%) of 45A, 48Al and 50Al, and ternary alloys of Ti-48Al containing 2Cr and 4Cr. Thermal cyclic oxidation was conducted discontinuously at temperatures of 7000C and 9000C in static laboratory air. Optical microscopy, Scanning Electron Microscopy (FESEM), Energy Dispersive Xray Analysis (EDX) and X-ray diffraction (XRD) techniques were employed for the analysis. SEM examination of cross-sectional samples using secondary electron and line-scan analysis after exposure at 7000C showed that non-adherent oxides scales formed due to the spallation caused by cyclic condition. While, exposure at 9000C, only binary alloys exhibited breakaway oxidation while the oxides scale formed on the ternary alloys were well-adhered on the substrate alloy. Overall, exposure at 9000C resulted in thicker and harder oxide scales and addition of Cr believed to improve oxidation resistance of Ti-Al based intermetallics at higher temperature